2022
DOI: 10.51698/aloma.2022.40.2.33-45
|View full text |Cite
|
Sign up to set email alerts
|

A cross cultural investigation of individuals’ acceptance of Smart Home Technology: The role of needs satisfaction

Abstract: Smart Home Technology manufacturers currently face significant issues with regard to the acceptance and intention to use their products. Evidence suggests that specific products have the lion’s share of the smart home market, and fully integrated smart home set-ups are still rare. The aim of this study was to investigate the acceptance of Smart Home Technology by administering the Technology Acceptance Model and applying Self Determination Theory with a sample of British (N = 284) and Spanish (N= 209) technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…It is interesting to note that, over the past twenty years or so, there has been an almost total inversion of the perception of the role of regionality in the development of smart cities. At one point, in the early 2000s, the smart city was considered a generic, and universally applicable, concept that was defined only by technology, rather than by geographical or cultural context [29,30]. In more recent years, however, as the global understanding of smart technologies has matured, and the idea of the smart sustainable city has begun to take shape, the criticality of local factors in the development of smart cities has begun to be recognised [47,48].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that, over the past twenty years or so, there has been an almost total inversion of the perception of the role of regionality in the development of smart cities. At one point, in the early 2000s, the smart city was considered a generic, and universally applicable, concept that was defined only by technology, rather than by geographical or cultural context [29,30]. In more recent years, however, as the global understanding of smart technologies has matured, and the idea of the smart sustainable city has begun to take shape, the criticality of local factors in the development of smart cities has begun to be recognised [47,48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In more recent years, however, as the global understanding of smart technologies has matured, and the idea of the smart sustainable city has begun to take shape, the criticality of local factors in the development of smart cities has begun to be recognised [47,48]. The social, economic and sustainability benefits of powerful and emerging communications technologies have been shown to vary according to geography and regional culture [49,50], and it has also been shown that smart services have higher rates of adoption when aligned to cultural preferences [29,30]. This stresses the point, already made, that smart sustainable city planners and strategists should prioritise the selection and adaption of culturally aligned technologies, if they are to maximise public acceptance and societal benefit [51,52].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation